Hydrogen‐Bonded Macrocyclic Supramolecular Systems in Solution and on Surfaces - Mayoral, María J. (ChemistryOpen, 2015)
Cyclization into closed assemblies is the most recurrent approach to realize the noncovalent synthesis of discrete, well‐defined nanostructures. This review article particularly focuses on the noncovalent synthesis of monocyclic hydrogen‐bonded systems that are self‐assembled from a single molecule with two binding‐sites. Taking advantage of intramolecular binding events, which are favored with respect to intermolecular binding in solution, can afford quantitative amounts of a given supramolecular species under thermodynamic control. The size of the assembly depends on geometric issues such as the monomer structure and the directionality of the binding interaction, whereas the fidelity achieved relies largely on structural preorganization, low degrees of conformational flexibility, and templating effects. Here, we discuss several examples described in the literature in which cycles of different sizes, from dimers to hexamers, are studied by diverse solution or surface characterization techniques.